Determining Factors in the Choice of Export Markets for Chemical Products (2020)
Taking into account the importance of business internationalization, the aim of this paper is to implement a multicriteria methodology using factors and variables found in the literature to assess the importance that the chemical sector gives them when selecting a market to export. Using a non-random sample of 10 chemical firms, the valuations of the businessmen were collected through telephone interviews and questionnaires, and finally the general and local valuation of each factor was obtained, as well as which countries were more suitable to carry out exports. The analyses show that most important factors for choosing a market in its order are: price at destination, transit time, international transport cost, import cost, and tariff barriers.